Conflitos geracionais e clima organizacional: desafios e oportunidades para o recursos humanos - IVO, Emilia Caroline Alvino Santana (251, 2024)
O presente trabalho tem como objetivo investigar como a diversidade geracional afeta o clima organizacional, abordando desafios e oportunidades para a gestão de Recursos Humanos. A pesquisa examina as diferenças comportamentais e emocionais entre as gerações Baby Boomers, X, Millennials e Z, identificando como essas diferenças podem gerar conflitos e impactar o ambiente de trabalho. Por outro lado, o estudo destaca o potencial de aproveitar essas diversidades como vantagem estratégica, promovendo inovação e colaboração. Utilizando uma metodologia bibliográfica, o trabalho fundamenta-se em teorias sobre inteligência emocional, clima organizacional e gestão de pessoas. São discutidas práticas como programas de mentoria intergeracional, diagnósticos regulares de clima e treinamentos que valorizam a integração e o respeito às diferenças geracionais. Os resultados esperados incluem a melhoria do clima organizacional, a retenção de talentos e o fortalecimento da produtividade por meio de uma abordagem que valoriza a diversidade. Assim, conclui-se que o sucesso dessa gestão depende de estratégias alinhadas às necessidades específicas de cada geração, garantindo um ambiente de trabalho harmonioso e inovador.

This study aims to investigate how generational diversity affects organizational climate, addressing challenges and opportunities for Human Resources management. The research examines behavioral and emotional differences among Baby Boomers, Generation X, Millennials, and Generation Z, identifying how these differences can generate conflicts and impact the workplace environment. On the other hand, the study highlights the potential to leverage these diversities as a strategic advantage, fostering innovation and collaboration. Using a bibliographic methodology, the work is based on theories of emotional intelligence, organizational climate, and people management. It discusses practices such as intergenerational mentoring programs, regular climate diagnostics, and training that emphasize integration and respect for generational differences. The expected outcomes include improving organizational climate, retaining talent, and enhancing productivity through an approach that values diversity. Thus, it concludes that the success of this management relies on strategies aligned with each generation's specific needs, ensuring a harmonious and innovative work environment.

This study aims to investigate how generational diversity affects organizational climate, addressing challenges and opportunities for Human Resources management. The research examines behavioral and emotional differences among Baby Boomers, Generation X, Millennials, and Generation Z, identifying how these differences can generate conflicts and impact the workplace environment. On the other hand, the study highlights the potential to leverage these diversities as a strategic advantage, fostering innovation and collaboration. Using a bibliographic methodology, the work is based on theories of emotional intelligence, organizational climate, and people management. It discusses practices such as intergenerational mentoring programs, regular climate diagnostics, and training that emphasize integration and respect for generational differences. The expected outcomes include improving organizational climate, retaining talent, and enhancing productivity through an approach that values diversity. Thus, it concludes that the success of this management relies on strategies aligned with each generation's specific needs, ensuring a harmonious and innovative work environment.
Keywords: Recursos humanos; Ambiente organizacional; Ambiente de trabalho; Gestão e Negócios